Lightweight key management scheme to enhance the security of internet of things. (1st January 2012) - Chen, Dong; Chang, Guiran; Sun, Dawei; Jia, Jie; Wang, Xingwei
Trillions things of Internet of Things (IOT) or Cyber-Physical Systems (CPS) employ a unique global addressing scheme to interact to each other and corporate with others to provide intelligent services. However, people may resist the IOT as long as there is no public confidence that it will not cause any serious threats to their privacy. An effective secure key management for things authentication is the prerequisite of the security operations. Studying on the characteristics of things in the IOT deeply, this paper proposes a lightweight security key management scheme for Things to Things (T2T) communication in wireless networks of IOT which are usually composed of heterogeneous sensors/actuators or smart sensor-embedded things. Eventually, we evaluate the proposed scheme on storage overhead, communication overhead, computation overhead and resilience against nodes compromise attack, respectively.